Therapeutic use of transferrin to modulate anemia and conditions of iron toxicity. Issue 6 (November 2017) - Boshuizen, M.; van der Ploeg, K.; von Bonsdorff, L.; Biemond, B.J.; Zeerleder, S.S.; van Bruggen, R.; Juffermans, N.P.
Abstract: As the main iron transporter, transferrin delivers iron to target tissues like the bone marrow for erythropoiesis. Also, by binding free iron, transferrin prevents formation of reactive oxygen species. Transferrin deficiency due to congenital hypotransferrinemia is characterized by anemia as well as oxidative stress related to toxic free iron. Transferrin supplementation may be beneficial in two ways. First, transferrin can correct anemia by modulating the amount of iron that is available for erythropoiesis. This is obvious for patients that suffer from hypotransferrinemia, but may also have beneficial effects for β-thalassemia patients. Second, under conditions of iron overload, transferrin reduces oxidative stress by binding free iron in the circulation and in tissues. Hereby, transferrin protects the host against the reactive oxygen species that can be formed as a consequence of free iron. This beneficial effect is shown in hematological patients undergoing chemotherapy and stem cell transplantation. Transferrin may also be beneficial in lung injury, ischemia-reperfusion injury and hypomyelination. This review summarizes the preclinical and clinical data on the efficacy of exogenous transferrin administration to modulate certain forms of anemia and to prevent the toxic effects of free iron. Thereby, we show that transferrin has promising therapeutic potential in a wide variety of conditions.